2016
DOI: 10.1074/jbc.m115.697334
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Enhances Linkage in the Vascular Endothelial Calmodulin Network via a Feedforward Mechanism at the G Protein-coupled Estrogen Receptor 1

Abstract: Estrogen exerts many effects on the vascular endothelium. Calmodulin (CaM) is the transducer of Ca 2؉ signals and is a limiting factor in cardiovascular tissues. It is unknown whether and how estrogen modifies endothelial functions via the net-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 65 publications
0
49
0
Order By: Relevance
“…Recurrent inflammatory factors are known to play a role in breast cancer promotion and angiogenesis . The observation of upregulation of pro‐inflammatory cytokines IL‐6, IL‐1 and TNF in ER‐positive tumors demonstrated that these cytokines play an important role in the activation of ER . Activated ER promotes the release of vasodilators, leading to vasomotor disorders and neovascularization .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrent inflammatory factors are known to play a role in breast cancer promotion and angiogenesis . The observation of upregulation of pro‐inflammatory cytokines IL‐6, IL‐1 and TNF in ER‐positive tumors demonstrated that these cytokines play an important role in the activation of ER . Activated ER promotes the release of vasodilators, leading to vasomotor disorders and neovascularization .…”
Section: Discussionmentioning
confidence: 99%
“…35,36 The observation of upregulation of pro-inflammatory cytokines IL-6, IL-1 and TNF in ER-positive tumors demonstrated that these cytokines play an important role in the activation of ER. 50,51 Activated ER promotes the release of vasodilators, leading to vasomotor disorders and neovascularization. 52 Moreover, studies have shown that several autoimmune disorders are associated with ER-positive breast cancer, 52 suggesting a potential relationship between immune abnormalities and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As to G βγ initiated ERK1/2 transactivation, this cascade includes Src ‐mediated activation of matrix metalloproteinases (MMPs) accompanied by the release of heparin‐bound epidermal growth factor (EGF) and the activation of the EGF receptor (EGFR), followed by the activation of extracellular signal‐regulated kinase 1/2 (ERK1/2) and phosphoinositide 3‐kinase (PI3K) . G βγ transactivation of ERK1/2 and PI3K can activate endothelial nitric oxide synthase (eNOS) in a mitogen‐activated protein kinase (MAPK)‐dependent manner . eNOS activation is followed by increased NO production which can recruit pain sensitizing molecules .…”
Section: Features Of Gpermentioning
confidence: 99%
“…In addition to changes in SERCA and PLB expression/phosphorylation profiles, the improvement in cardiac function with G1 treatment in these models could also be due in part to improvements in endothelial nitric oxide synthase (eNOS) activity and vascular tone. The effects of G1 on the vascular endothelium likely involve stimulation of Ca 2+ /calmodulin signaling network activities (87), including GPER activation per se (87,88), upregulation of the Ca 2+ -dependent interaction between eNOS and calmodulin (87), improvement in the eNOS phosphorylation profile (87,89), and optimization of vascular Ca 2+ signaling via combined effects on influx (90) and efflux pathways (91).…”
Section: Estrogen Gper and Serca2a And Its Regulatory Proteinsmentioning
confidence: 99%